School Well-Being and Achievement Motivation among Senior High School Students - Fernindo Maha, Marlay; Tiovania, Evelyn; Valeria Sitorus, Cindy; Stefani Purba, Regina; Harapan Yosua Marpaung, Binsar; Astri Tarigan, Beby; Marpaung, Winida (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
This study highlights the importance of students’ psychological conditions in supporting academic success, particularly in relation to school well-being and achievement motivation. The research involved 127 senior high school students and applied a quantitative correlational approach. Data were collected using Likert-scale instruments measuring school well-being and achievement motivation, and analyzed through Pearson correlation. The findings revealed a positive and significant relationship between the two variables, with most students categorized at high levels of both school well-being and achievement motivation. Further analysis indicated that different dimensions of school well-being contribute differently to motivational aspects, where environmental and social factors are more associated with openness to feedback, while health and facility-related conditions are linked to persistence and creativity. Overall, the results suggest that school well-being plays a meaningful role in shaping students’ achievement motivation and should be considered in efforts to improve educational environments.Penelitian ini berangkat dari meningkatnya perhatian terhadap aspek psikologis siswa dalam mendukung keberhasilan belajar, khususnya terkait kesejahteraan di sekolah dan motivasi berprestasi. Penelitian ini melibatkan 127 siswa sekolah menengah atas dengan menggunakan pendekatan kuantitatif korelasional. Data dikumpulkan melalui skala Likert yang mengukur school well-being dan motivasi berprestasi, kemudian dianalisis menggunakan teknik korelasi Pearson. Hasil analisis menunjukkan adanya hubungan positif dan signifikan antara kedua variabel, dengan mayoritas siswa berada pada kategori tinggi baik dalam kesejahteraan sekolah maupun motivasi berprestasi. Temuan lanjutan memperlihatkan bahwa beberapa aspek kesejahteraan sekolah berkontribusi berbeda terhadap dimensi motivasi, di mana kondisi lingkungan dan relasi sosial lebih berkaitan dengan keterbukaan terhadap umpan balik, sementara kondisi kesehatan dan dukungan fasilitas lebih terkait dengan ketekunan dan kreativitas. Secara umum, hasil ini menunjukkan bahwa kesejahteraan sekolah memiliki peran penting dalam membentuk motivasi berprestasi siswa, sehingga perlu menjadi perhatian dalam pengembangan lingkungan pendidikan yang lebih optimal.